Peran Pemerintah Daerah Dalam Pelaksanaan Kabupaten Magetan Layak Anak (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Abstract. This research aims to determine the implementation of a Child Friendly District (KLA) in Magetan Regency. The implementation of the role of the Magetan Regency Government is to implement and carry out policies in implementing and developing a Child-Friendly Magetan Regency and knowing what factors are obstacles and drivers of the regional government's role in implementing a Child-Friendly Regency in Magetan Regency. This research was conducted using empirical or non-doctrinal law using primary data in the form of interviews with regional officials of Magetan Regency as well as the results of field observations conducted in Magetan Regency. Secondary data used in this research are legal materials in the form of articles, journals and other legal literature related to the research being discussed. The role of regional government in implementing KLA is an implementation of obligations that have been regulated in Government Regulation Number 12 of 2022 concerning the Implementation of Child Friendly Districts/Cities, and in its implementation the role of regional government is regulated directly in the policies governing Magetan Regency, this is specifically regulated in Magetan Regency Regional Regulation Number 1 of 20222 concerning the Implementation of a Child Friendly Regency.